From here to eternity - Barthalon, Eric (2003)
This article offers a critical reflection on the character and significance of financial crises, drawing on the work of various thinkers who have examined this issue. After defining a financial "crisis", the article asks three questions: Are financial crises foreseeable? Can and should they be contained? How can they be prevented? The first section reviews the various mechanisms that lead to a crisis situation. The second analyzes the role of the lender of last resort and the three dilemmas it faces, relating respectively to moral hazard, the bearing of losses by the community, and the handling of the assets obtained from such a lender's intervention. The last part presents the various proposals that have been made for the prevention of crises - some of them based on the existing monetary institutions, others more radical. - Reproduced.
Keywords: Economic recession